Viruses as Modulators of Mitochondrial Functions - Sanjeev K. Anand; Suresh K. Tikoo (Advances in Virology)
Mitochondria are multifunctional organelles with diverse roles including energy production and distribution, apoptosis, eliciting host immune response, and causing diseases and aging. Mitochondria-mediated immune responses might be an evolutionary adaptation by which mitochondria might have prevented the entry of invading microorganisms thus establishing them as an integral part of the cell. This makes them a target for all the invading pathogens including viruses. Viruses either induce or inhibit various mitochondrial processes in a highly specific manner so that they can replicate and produce progeny. Some viruses encode the Bcl2 homologues to counter the proapoptotic functions of the cellular and mitochondrial proteins. Others modulate the permeability transition pore and either prevent or induce the release of the apoptotic proteins from the mitochondria. Viruses like Herpes simplex virus 1 deplete the host mitochondrial DNA and some, like human immunodeficiency virus, hijack the host mitochondrial proteins to function fully inside the host cell. All these processes involve the participation of cellular proteins, mitochondrial proteins, and virus specific proteins. This review will summarize the strategies employed by viruses to utilize cellular mitochondria for successful multiplication and production of progeny virus.